SCIFI – A Software-Based Controller for Efficient Wireless Networks - Magalhães, Luiz Claudio Schara; Balbi, Helga Dolorico; Corrêa, Cosme; Valle, Rafael De Tommaso do; Stanton, Michael (My University, 2013)
SCIFI is an open source software wireless controller. Large scale wireless networks that use low cost (SOHO) Access Points are hard to install and run due to the complexity of configuring and monitoring many APs with a distributed interface, coupled with the difficulty of creating a good network configuration with no help from the system. On the other hand, hardware controllers and their compatible APs are too expensive, proprietary and ultimately tie the buyer to a single vendor. SCIFI allows the use of inexpensive hardware to create large scale wireless installations. This paper describes the SCIFI algorithms, its interface, the current deployment at UFF and the future work planned for SCIFI.
Keywords: IEEE 802.11; wireless network deployment; AP controller; scifi